Peningkatan Sikap Cinta Tanah Air Melalui Model Pembelajaran Value Clarification Technique (VCT) Pada Mahasiswa PGSD - Anantama Dewantoro (PGSD FKIP UPR, 2022)
This research aims to improve the attitude of love for the homeland of PGSD UMG students using the Value Clarification Technique learning model for 4th semester students. This type of research is classroom action research. The design of this study used the Kemmis & Mc Taggart model. The research subjects included 4th semester students of class A morning PGSD UMG with a total of 40 students. The object of this study is the attitude of love for the homeland of pgsd students. Data analysis techniques are descriptively quantitative. The results of this study show that there is an increase in the attitude of love for the homeland of students. This can be inferred from several cycles that have been carried out. Cycle I to II values on indicator 1 from 76.76% to 78.48%, indicator 2 from 75.33% to 77.58%, and indicator 3 from 63.57% to 74.39%. In subsequent studies, from cycle II to III, results were obtained on indicator 1 from 76.48% to 78.67%, indicator 2 from 76.58% to 78.62%, and indicator 3 from 64.39% to 67.14%. Meanwhile, from cycle II to IV, results were obtained, namely indicator 1 from 74.67% to 83.33%, indicator 2 from 75.62% to 82.91%, and indicator 3 from 74.14% to 78.59%.